Aprendizaje kinestesico y su incidencia en el rendimiento escolar de los estudiantes del tercer año de la Escuela de Educación Básica Aurora Estrada Y Ayala De Ramírez Pérez de la ciudad de Babahoyo. - Salcedo Salinas, Sasha Sofia (2018)
There are many ways that teachers develop teaching strategies, as well as the ways in which students learn, it is necessary to review the activities carried out in classes and the types of learning with which students are defined, which would facilitate the educational work and the conditions in which students interrelate in the teaching-learning process. In the present research work is intended to show the influence of kinesthetic learning on school performance of the third year students of the School of Basic Education Aurora Estrada and Ayala Ramirez Perez of the city of Babahoyo in the school period 2017 - 2018, for which it is necessary to determine the methodology, using for this case the type of exploratory, descriptive and explanatory research applied in a systematic way according to the needs, the inductive and deductive methods, the techniques of information collection beginning with the observation, the compilation of the bibliographic information, then with interviews and surveys, whose instrument was the semi-structured questionnaire, open and closed, in a formal and informal way. It should be noted that among the conclusions it is stated that there are few teachers who include playful activities in the teaching-learning process and that students present inappropriate behaviors, which hinders their application and obtaining positive results, for this reason the proposal for the development of a manual for the application of recreational activities to control student behavior and improve the teaching-learning process.